Factors Affecting Baby Boomers’ Attitudes towards the Acceptance of Mobile Network Providers' AI Chatbot - Nanticha Poonpanich; Jiroj Buranasiri (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2022)
The research aims to study the factors which affect baby boomers’ attitudes towards the acceptance of mobile network providers’ Artificial Intelligence (AI) Chatbots in Thailand and their influences. The research sample consists of 400 people who were born from 1946 to 1964 and had experience in using AI chatbots. The proposed concept of model of this research is based on the Technology Acceptance Model (TAM), Modified Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), and Innovation Diffusion Theory (IDT). The questionnaire is the tool for data collection. The statistics for data analysis were mean, percentage, frequency distribution, and standard deviation. The statistical hypothesis testing included confirmatory factor analysis and structural equation model. The results can prove the importance of perceived usefulness, perceived ease of use, compatibility, privacy concern, attitude toward advertisement, and social influence on the acceptance of AI chatbot technology. Consequently, the results help business sectors to form better strategies to promote the broader use of AI chatbots.